Նորահայտ տապանաքարեր Սոթքից - Ավետիս Գրիգորյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Данная работа посвящена проблемам анализа, семантики и датировки барельефов надгробных плит, недавно открытых в деревне Сотк Гегаркуникской области. This work is devoted to the problems of analysis, semantics and dating of images of tombstone sculptures recently discovered in the village of Sotk, Gegharkunik region.
Keywords: History; Fine Arts; Sepulchral Monuments